Leaf and canopy photosynthesis models for cocksfoot (Dactylis glomerata L.) grown in a silvopastoral system - Peri, Pablo Luis (Lincoln University, Nueva Zelanda, 2019)
Tesis para obtener el grado de Doctor of Philosophy (PhD) en Agricultural Sciences, de Lincoln University (New Zealand), en 2002